2014
DOI: 10.1177/0218492314523971
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic epidermoid cyst: A very rare condition

Abstract: A 65-year-old man presented with a nonspecific thymic neoplasm following blunt thoracic trauma. The lesion increased in size over 12 years, to reach 47 mm in diameter. After thymectomy, the lesion was described as an epidermoid lining cyst composed of thickened stratified squamous epithelium. We assume that this rare pathological condition was caused by skin tissue islands and fat migrating into the mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Our case showed a non-enhancing heterogeneous attenuated mass with a focal area of high attenuation in the peripheral portion of the mass, located in the anterior mediastinal area on CT images; there were no calcifications or fat components. Monaco et al ( 8 ) also reported a case of thymic epidermoid cyst showing high-attenuation foci within the mass on CT images. Epidermoid cysts usually include debris, keratin, and cholesterol ( 9 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our case showed a non-enhancing heterogeneous attenuated mass with a focal area of high attenuation in the peripheral portion of the mass, located in the anterior mediastinal area on CT images; there were no calcifications or fat components. Monaco et al ( 8 ) also reported a case of thymic epidermoid cyst showing high-attenuation foci within the mass on CT images. Epidermoid cysts usually include debris, keratin, and cholesterol ( 9 ).…”
Section: Discussionmentioning
confidence: 96%
“…Acquired thymic epidermoid cysts are considered to be the result of epidermal tissue migration into the anterior mediastinum with subsequent proliferation within the thymus ( 5 7 ). A few case reports have assumed that traumatic or surgical implantation of epidermal cells within the anterior mediastinum results in rare presentation of epidermoid cysts ( 7 8 ). For congenital epidermoid cysts, they might be potentially formed in the thymus, as in other locations ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, epidermoid cysts of the thymus are an extremely rare histological variant and are described only in a few cases in the literature, which is why it is rarely included in the differential diagnosis. [11][12][13][14] Since it is often difficult to make a conclusion based on imagistic examination the patients are operated in order to obtain a histology result and reliably exclude an oncological process.…”
Section: Discussionmentioning
confidence: 99%
“…This was thought to result from the introduction of epidermoid cells into the thymus following trauma [4]. Epidermoid tissue may be introduced in the thymus following surgery as well.…”
Section: Discussionmentioning
confidence: 99%